Affordable Housing, Disasters, and Social Equity: LIHTC as a Tool for Preparedness and Recovery. Issue 1 (2nd January 2020) - Mehta, Aditi; Brennan, Mark; Steil, Justin
Abstract: Problem, research strategy, and findings: The Low-Income Housing Tax Credit (LIHTC) is the most common financing mechanism for subsidized housing production in America. We investigate how and to what extent states are currently using the LIHTC to prepare for and recover from disasters. We systematically code guidelines in the 2017 LIHTC qualified allocation plans from 53 states and territories to identify disaster-related provisions. Twenty-four states and territories include provisions for preparedness or recovery in their allocation plans, of which 13 include only preparedness provisions, 3 include only recovery provisions, and 8 include both types. Preparedness provisions address project design and siting, whereas recovery provisions direct credits to disaster-affected areas or the replacement of damaged units. Using t tests, we compare three sets of states—those without any disaster-related provisions, those with either preparedness or recovery provisions, and those with both types of provisions—across measures of housing cost, demographic composition, disaster exposure, and political ideology. States with higher homeownership rates, lower home values, and lower rents are more likely than other states to have either or both types of provisions. Future research should investigate state adoption of disaster-related LIHTC provisions to better inform affordable housing policy. Takeaway for practice: State governments could mitigate disaster-related hazards and help speed recovery by including locally relevant preparedness and recovery provisions in their LIHTC allocation plans. These provisions could encourage resilient construction, weigh the social costs and benefits of LIHTC construction in floodplains, or waive program rules to address postdisaster housing shortages.